2013
DOI: 10.3109/09638288.2013.780641
|View full text |Cite
|
Sign up to set email alerts
|

ICF profiling of patients with traumatic brain injury: an international professional survey

Abstract: People that suffered a traumatic brain injury (TBI) may have a variety of sequelae that impair functioning. The International Classification of Functioning, Disability and Health (ICF) can help in providing information regarding the identification of patients problems and needs as well as planning, implementing and coordinating the rehabilitation process. The ICF provides a frame of reference process illustrated as the rehabilitation cycle that can help during the rehabilitation process in goal setting bringin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 32 publications
0
5
0
2
Order By: Relevance
“…The study also demonstrates that individual goals may be categorized into five domains of the ICF-CY, hence allowing for comparison of studies by establishing a universal language (28). For example, the ICF-CY domains in our study have a higher proportion of activity-participation and a lower proportion of body function domain goals than for children with cerebral palsy (16) and for adults with acquired brain injury (29). Knowledge of the chosen domains of set goals also provides an opportunity to encourage change in goals as the child grows older, for example, to increase goals that include 'the child's active participation in the community' (5).…”
Section: Discussionmentioning
confidence: 68%
“…The study also demonstrates that individual goals may be categorized into five domains of the ICF-CY, hence allowing for comparison of studies by establishing a universal language (28). For example, the ICF-CY domains in our study have a higher proportion of activity-participation and a lower proportion of body function domain goals than for children with cerebral palsy (16) and for adults with acquired brain injury (29). Knowledge of the chosen domains of set goals also provides an opportunity to encourage change in goals as the child grows older, for example, to increase goals that include 'the child's active participation in the community' (5).…”
Section: Discussionmentioning
confidence: 68%
“…Similar results have been noted in previous studies linking concepts from expert surveys to ICF categories. [18][19][20] The critical factors that were identified by the experts in amputee rehabilitation working in different health care settings were similar across the six countries.…”
Section: Discussionmentioning
confidence: 88%
“…Another advantage of using the TBI ICF Core Sets as a guide for the assessment is that it improves quality assurance of assessing the four different domains that interact in functioning. For example, research has shown that professionals tend to assess according to their area of knowledge (Laxe et al, 2014) and environmental factors that have a significant effect on functioning are not systematically assessed (Hoffman et al, 2014;Laxe et al, 2012).…”
Section: The Clinical Implementation Of Icf In Tbimentioning
confidence: 99%